2022
DOI: 10.1038/s41598-022-21568-8
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, physicochemical characterization, and bioactivity evaluation of berberine-entrapped albumin nanoparticles

Abstract: Berberine (BBR) is an isoquinoline alkaloid with several clinical therapeutic applications. Its low water solubility, absorption, and cellular bioavailability diminish BBR's therapeutic efficacy. In this study, BBR was encapsulated into bovine serum albumin nanoparticles (BSA NPs) core to reduce BBR limitations and enhance its clinical therapeutic properties. Several physicochemical characterization tools, such as Dynamic Light Scattering and Ultraviolet–Visible spectroscopic measurements, field emission trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…Overall, platinum core in the nanocomposite may catalyse the antioxidant action, whereas RSV donates hydrogen and scavenges free radicals, while BSA coating enhances nanoparticle stability and bioavailability. Overall, the interaction between RSV and the PtNP’s surface may improve antioxidant capacity synergistically 41 , 47 , hence explaining the better anti-oxidant activity of Pt-BSA-RSV NPs composite as compared to the individual RSV or PtNPs.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, platinum core in the nanocomposite may catalyse the antioxidant action, whereas RSV donates hydrogen and scavenges free radicals, while BSA coating enhances nanoparticle stability and bioavailability. Overall, the interaction between RSV and the PtNP’s surface may improve antioxidant capacity synergistically 41 , 47 , hence explaining the better anti-oxidant activity of Pt-BSA-RSV NPs composite as compared to the individual RSV or PtNPs.…”
Section: Resultsmentioning
confidence: 99%
“…To further validate the contribution of the BBR regulated gut microbiota to HFD-associated colorectal tumourigenesis, we transferred fecal samples from HFD-fed mice, with or without BBR administration, to AOM/DSS-induced CRC mice with microbiota depletion through antibiotics treatment (Figure 8 A). Given that BBR bioavailability is very low in vivo 21 , 22 , high concentrations of BBR might have remained in the stool. To determine the content of BBR remaining in the stool before FMT, we used LC-MS to confirmed that the content of BBR remaining in fecal suspension was approximately 170 ug/ml on the basis of comparison with a BBR standard sample, which was significantly lower than the concentration of BBR (100mg/kg/d) directly treated in HFD-fed mice (Figure 8 B).…”
Section: Resultsmentioning
confidence: 99%
“…Berberine is a natural isoquinoline alkaloid isolated from Traditional Chinese herbs such as Coptis chinensis and Berberis vulgaris . Berberine is identified as a safe and curative agent to treat diabetes, hyperlipidemia, and pathogenesis of CVDs through upregulating cellular glucose and lipids metabolism, attenuating oxidative stress generation and inflammation, and inhibiting apoptotic signals ( Younis et al, 2022 , Wang et al, 2023 ). ER stress response potentiates myocardial cells apoptosis, cardiac remodeling, and heart failure.…”
Section: Discussionmentioning
confidence: 99%